Proposed score for survival of patients with myelodysplastic syndromes. (18th September 2013) - Sperr, Wolfgang R.; Kundi, Michael; Wimazal, Friedrich; Nösslinger, Thomas; Schönmetzler‐Makrai, Anabel; Stauder, Reinhard; Krieger, Otto; Neukirchen, Judith; Germing, Ulrich; Pfeilstöcker, Michael; Valent, Peter
Abstract Background Patient selection for various therapies in myelodysplastic syndromes (MDS) is based on prognostic factors, scoring systems and the individual life expectancy. However, most established risk scores include mainly disease‐related parameters and thus focus on leukaemia‐transformation rather than survival. Patients and Methods To establish a risk score optimized for prediction of survival, we analysed international prognostic scoring system (IPSS)‐related and IPSS‐independent variables in 400 patients with primary MDS (median age: 71 years; range 18–91) of the Austrian MDS platform. Patients were randomly split into a learning sample (60%) and validation sample (40%). External validation was performed on 93 patients from the Heinrich Heine University (Duesseldorf/Germany). Results By multivariate analysis, IPSS, ferritin, age and comorbidities were found to be independent predictive variables concerning survival. Based on weighing these prognostic parameters against each other, we established a novel survival score employing IPSS, ferritin (< 900 ng/mL = 0; ≥ 900 ng/mL = 1), age (< 70 years = 0; 70–79 years = 1; ≥ 80 years = 1·5) and HCT‐CI comorbidity (low/intermediate = 0; high = 0·5). Using this score, four prognostic risk groups could be discriminated in the validation sample, with highly significant differences in life expectancy [median survival: LowS (score 0), not reached; Int‐1S (score 0·5–1·0), 3·84 years; Int‐2S (score 1·5–2·0): 2·72 years; and HighS (score > 2·0): 0·80 years; P < 0·0001]. Conclusions Our newly proposed score may be a useful tool for survival prediction in MDS and helpful in patient selection for various therapies in daily practice and clinical trials.